Influence of specimen size and microstructure on uniaxial compression of WC-Co micropillars. Issue 13 (September 2019) - Sandoval, D.A.; Rinaldi, A.; Notargiacomo, A.; Ther, O.; Tarrés, E.; Roa, J.J.; Llanes, L.
Abstract: The current interest on the development of components on the micrometer size regime demands the evaluation of the mechanical behavior at such small length scales. Regarding cemented carbides, evaluation of mechanical properties at the micrometer scale is a relatively unexplored subject. In the present work we propose and validate a testing protocol based on uniaxial compression of micropillars milled by focused ion beam, to evaluate the elastic and plastic response of WC-Co alloys. In doing so, we studied three WC-Co alloys: fine, medium and coarse grained. First, we determined an appropriate Representative Elementary Volume (REV) to consider the tested sample as a bulk. Then, we performed uniaxial compression on the micropillars that met that REV. Based on the stiffness recorded for each micropillar, we found that the estimated elastic modulus for the fine and medium grained alloys is within the range expected for WC-Co alloys with a similar volume fraction of constitutive phases as those studied here. Finally, we stablished a correlation among stress-strain response, microstructure and yielding within constitutive phases by linking strain bursts taken place at different stress levels to plastic deformation/damage features observed in the micropillars after uniaxial compression.